MANAJEMEN SUMBER DAYA PENDIDIKAN PADA SEKOLAH DASAR DAERAH TERPENCIL DI SDN 2 BUTUT SAPAU - Melania Sofyan; Musyarapah Musyarapah; Santi Erliana (STKIP Pesisir Selatan, 2026)
This study aims to analyze the management of educational resources at SDN 2 Buntut Sapau, an elementary school located in a remote area with various limitations in infrastructure, human resources, and access to technology. The research focuses on three main aspects: human resource management, educational facilities and infrastructure management, and the management of technology and school administration resources. This study employed a qualitative approach using a case study design. Data were collected through semi-structured interviews, observations, and documentation involving the principal and teachers as research informants. The collected data were analyzed using the interactive model of data analysis, including data reduction, data display, and conclusion drawing. The findings reveal that human resource management is implemented through task distribution, teacher empowerment, collaboration among school personnel, and independent professional development despite limited staffing. Facilities and infrastructure management is carried out by optimizing available resources, utilizing the surrounding environment as a learning resource, and prioritizing essential educational needs. Meanwhile, technology and administrative resources are managed adaptively through limited digital technology utilization, alternative energy sources, and flexible administrative practices adjusted to local conditions.